The Appropriation of Islamic Literacy by Middle-class Muslims in Jogokariyan and Sudirman Mosques, Yogyakarta - Abd. Aziz Faiz (JSW (Jurnal Sosiologi Walisongo), 2023)
Since 1980, the Islamic literacy of the Sudirman Mosque, Yogyakarta has centered around jihadi ideology, while the Jogokariyan Mosque, Yogyakarta has been normative and oriented toward Islamization. Of late, the Sudirman and the Jogokariyan Mosques are taking new and different approaches to Islamic literacy. This study aims to describe the newly adopted approaches and their appropriation within the middle-class society and the urban Islamic landscape. This research is qualitative-descriptive, using post-Islamism as a theoretical concept. This study highlights two important findings. First, the Sudirman Mosque takes a progressive approach by discussing philosophy and postcolonialism and publishing reflective Islamic literature, while the Jogokariyan Mosque popularizes Islam through spiritual recreation, hijrah festivals, and publishing normative Islamic pop literature. Second, these new approaches to Islamic literacy appropriate urban characteristics and the congregations’ social classes. These findings contribute to mapping new Islamic literacy patterns in Yogyakarta.